2004
DOI: 10.1210/me.2003-0044
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Targets of Nuclear Estrogen Receptors

Abstract: Estrogen influences the physiology of many target tissues in both women and men. The long-term effects of estrogen are mediated predominantly by nuclear estrogen receptors (ERs) functioning as DNA-binding transcription factors. Tissue-specific responses to estrogen therefore result from regulation of different sets of genes. However, it remains perplexing as to what regulatory sequence contexts specify distinct genomic responses. First, this review classifies estrogen response sequences in mammalian target gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
301
1
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(319 citation statements)
references
References 112 publications
8
301
1
9
Order By: Relevance
“…We have known from previous studies that E2-stimulated breast cancer cell proliferation involves ERα-mediated regulation of several key cell cycle regulatory genes (Coser et al, 2003;Ngwenya et al, 2003;O'Lone et al, 2004;Eeckhoute et al, 2006). Aberrant DNA methylation of tumor suppressor genes has been reported in many major types of cancer with potential involvement in the inactivation of regulatory cell cycle and apoptosis genes.…”
Section: Discussionmentioning
confidence: 99%
“…We have known from previous studies that E2-stimulated breast cancer cell proliferation involves ERα-mediated regulation of several key cell cycle regulatory genes (Coser et al, 2003;Ngwenya et al, 2003;O'Lone et al, 2004;Eeckhoute et al, 2006). Aberrant DNA methylation of tumor suppressor genes has been reported in many major types of cancer with potential involvement in the inactivation of regulatory cell cycle and apoptosis genes.…”
Section: Discussionmentioning
confidence: 99%
“…These include the direct binding to EREs to activate transcription and indirect binding to AP-1, SP1 and GATA binding proteins to coactivate the expression of genes. 32,33 In other words, estrogen can directly and indirectly regulate the expression of ACSL6 and IL3 genes. In one report, sex-specific expression of IL3 was found in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is now known that one-third of the categorized human 17β-estradiol-responsive genes are transcribed via indirect ER-DNA association through proteinprotein interactions with several transcription factors (13). Both ERα and ERβ can exert transcriptional regulation by tethering to other transcription factors such as c-Fos/c-Jun (activator protein-1, AP-1), Sp1, or NF-κB without themselves binding to EREs on DNA (13)(14)(15)(16)(17)(18). Genome landscaping has revealed that the non-ERE-dependent mode of transcription is the preferred pathway used by ERβ to regulate transcription of its target genes.…”
mentioning
confidence: 99%